Annual Plan, 1990-91 Orissa Vol. I - Planning Commission (Planning Commission, 1989)
The current year (1989-90) is the final year of the 7th Plan. The approved outlay for the 7th Plan of Orissa is Rs. 2,700’0 Crores. In percapita terms, this outlay amounts to Rs. 931’00 Crores, against this outlay, it is expected that the total 7th plan performance may amount to Rs. 3,377'00 Crores keeping in view the magnitude of poverty and under development of the State, priority has been accorded during the 7th Plan to the schemes for poverty eradication, expansion of employment opportunity and augmentation of agricultural and industrial production, Emphasis has also been laid down on development of infrastructure via. additional irrigation facilities, generation of more power to meet the growing demand and expansion of housing facilities. A review of the performance and impact of the 7th plan involves an analysis of the changes in important indicators of socio-economic development, The most important indicators among others, are the rate of growth of the State domestic product/State income, growth of percapita state income, production and productivity of major agricultural products, the quantum of employment generated and the percentage’ of population brought above the poverty line.
Annual Plan, 1990-91 Orissa Vol. I
Government of Orissa